2006
DOI: 10.1002/ajpa.20421
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of craniofacial integration in extantHomo,Pan, andGorilla

Abstract: Brain size increased greatly during Pleistocene human evolution, while overall facial and dentognathic size decreased markedly. This mosaic pattern is due to either selective forces that acted uniquely on each functional unit in a modularized, developmentally uncoupled craniofacial complex, or alternatively, selection that acted primarily on one unit, with the other responding passively as part of a coevolved set of ontogenetically and evolutionarily integrated structures. Using conditional independence modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 59 publications
0
42
1
Order By: Relevance
“…Covariance patterns are similar across human populations (22), and although there are some important differences, African apes and humans have broadly similar covariance patterns (23)(24)(25). The sum suggests that it is reasonable to assume that Neandertals would have had similar covariance patterns to humans, at least for most features.…”
Section: Single Features Vs Complexes Of Featuresmentioning
confidence: 98%
“…Covariance patterns are similar across human populations (22), and although there are some important differences, African apes and humans have broadly similar covariance patterns (23)(24)(25). The sum suggests that it is reasonable to assume that Neandertals would have had similar covariance patterns to humans, at least for most features.…”
Section: Single Features Vs Complexes Of Featuresmentioning
confidence: 98%
“…Graphical modeling is another useful method for exploring the structure of integration (Magwene 2001;Young 2004;Young and Hallgrímsson 2005;Polanski and Franciscus 2006;Allen 2008;Lawler 2008;Zelditch et al 2009;Webster and Zelditch 2011; but see criticisms by Bookstein 2007, 2009; reply by Magwene 2009). The analysis is done by analyzing correlations among pairs of variables, conditional on all others.…”
Section: Graphical Modelingmentioning
confidence: 99%
“…This matrix can be obtained by inverting the observed correlation matrix and rescaling the values so that elements along the diagonal are all 1.0. Magwene (2001) showed that graphical modeling can be useful for studying morphological integration, clarifying both concepts of modularity and revealing the structure of integration, and several recent empirical studies have used this method to test theories of integration/modularity (e.g., Young 2004;Young and Hallgrímsson 2005;Polanski and Franciscus 2006;Allen 2008;Lawler 2008).…”
Section: Graphical Modelingmentioning
confidence: 99%